THE CONCEPT OF JUSTICE IN ISLAMIC ECONOMICS: REALIZING SOCIAL AND ECONOMIC BALANCE - Ritonga, Miftahul Janna; Azzaki, Muhammad Adnan (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This article explores the concept of justice in Islamic economics, which is based on Islamic principles to achieve social and economic balance. Justice in Islamic economics encompasses wealth distribution, fair transactional relationships, and the protection of individual rights in economic activities. The discussion begins by identifying key principles of justice, including equitable resource distribution, fairness in profit sharing, and the prevention of exploitation in economic transactions. The application of this concept is seen in Islamic financial institutions that avoid riba (interest) and use profit-sharing systems, as well as in Islamic investments based on principles of halal and social benefits. Additionally, economic empowerment through zakat, alms, and charity plays a crucial role in achieving social justice. While this concept offers an alternative economic system that is fairer, this article also addresses challenges in its implementation, such as the lack of adequate legal infrastructure and the dominance of the global capitalist economy. Overall, Islamic economics has the potential to create a more just and inclusive economic system.